Application of the technique of defivatives into electricity market - Yun, Tae-Sik (KDI School, 1999)
Human effort to deal with the uncertainty and risk has kept on as long as human history. As the globalization of markets has progressed, the use of derivatives market such as swaps, futures and options in the advanced nations has become a common business practice as an effective and efficient means of hedging against volatile price changes and risk management. In a risk management tool, derivatives have originally been the way used to hedge commodities like food produce and metals. Derivatives now gradually form a major part of today''s financial markets and commodities markets either in Korea. Not only do they create leverage, but also they can simplify and speed up trading. To trade them with relatively small cost either makes them very attractive investments. They have enormously influenced over the current markets
Thesis(Master) --KDI School:Master of Strategy & International Management,1999